Investigation of capacitance dependence on droplet volume in MEDA based biochips - Shukla, V. (Institute of Electrical and Electronics Engineers Inc., 2017)
Digital microfluidics biochips has led to the revolution of modern day clinical diagnostics procedures. These biochips enable the use of nano-liter volume of samples and reagents. A more recent architecture of digital microfluidics known as Micro-electrode Dot Array (MEDA) has been introduced which incorporate some advance operations like diagonal movement and channel based routing. Owing to this new architecture, there exist some defects which require additional testing techniques. The defect in these biochips is studied by analyzing the capacitance changes at the sensing circuit. An investigation of capacitance of droplet based on the volume variation is done. The motivation behind this study is to see the variation of capacitance due to the defects in the biochips which can occur due to the volume variation of the droplet in MEDA based biochips. It is seen that the capacitance of droplet varies linearly with droplet volume which leads to the conclusion that defects due to the volume variation directly affects the capacitance at the sensing circuit. © 2016 IEEE.